Does the IMF help or hurt? The effect of IMF programs on the likelihood and outcome of currency crises - Axel Dreher; Stefanie Walter (ETH Zurich, KOF Swiss Economic Institute, 2008)
Using panel data for 68 countries over the period 1975-2002 this paper examines how IMF programs, disbursed loans, and compliance with conditionality affect the risk of currency crises and the outcome of such crises. Specifically, we investigate whether countries with previous IMF intervention are more likely to experience currency crises. In a second step, we analyze the IMF's impact on a country's decision to adjust the exchange rate, once a crisis occurred. We find that IMF involvement reduces the probability of a crisis. Once in a crisis, IMF programs significantly increase the probability that the authorities devalue the exchange rate. The amount of loans and compliance with conditionality have no impact. Our results suggest that the IMF - contrary to the Fund's critics - does indeed fulfill its functions of promoting exchange rate stability and helping its members to correct macroeconomic imbalances.
Keywords: F33; F34; O57; 330; IMF programs; growth; compliance; conditionality; Anpassungsprogramm des IWF; Makroökonomischer Einfluss; Währungskrise; Wechselkurspolitik; Wirtschaftswachstum; Welt